Sobre el origen de las fórmulas honoríficas con el sufijo -ísimo - Zieliński, Andrzej (Rzym a Półwysep Iberyjski: Różnorodność relacji od starożytności po współczesność, 2019)
The purpose of this paper is to explore and analyze diachronically honorific expressions with the superlative suffix -ísimo, whose origin corresponds to a pattern of lexicalization that reflects the interpersonal relations of the strongly stratified society of that time. In fact, the feudal pyramid, established since the fifth century AD, which places the highest classes at the highest point, is in clear correspondence with the conceptual metaphor “more is above”. Through analysis of a relatively large corpus of Latin (5th–12th centuries) and Spanish (13th– 16th centuries) texts, I will try to find the main reasons that came to determine its use in the Castilian language.